PENERAPAN MODEL PENGELOLAAN BISNIS OLAHAN PISANG PADA KELOMPOK WANITA TANI DESA MEKAR BUANA, KARAWANG (Universitas Esa Unggul, 2022)
Mekar Buana Village, Karawang Regency has a Women Farmers Group (KWT) which is active in producing natural products of bananas for processing such as chips, sale, and so on. Banana products from farmer groups in Mekar Buana Village have great potential for business development. Various types of bananas are owned, namely: jackfruit, uli, ambon, and moli. However, the problem is that there is still a lack of knowledge on banana processing and the management of the banana business has become an economic value and can become a leading commodity in Mekar Buana Village. The following are the problems of farmer groups and banana farming businesses as follows: they have not optimally managing business processes of innovative products, and go digital and e-commerce technology in the sales, supply chain and marketing processes. The method of implementing the activity is in the form of training on sustainable business management in implementing the Business Model Canvas (BMC), such as to 1). maintain the quality of processed banana products, 2). together with BUM-Des formed new business groups by providing training to encourage production, marketing, and facilitate the management needs of business groups, 3). regularly discuss business problems to strengthening business management group and business independence. Keywords: Business Management, Business Model Canvas, Farmer Women's Group